2009
DOI: 10.1108/17563780910982725
|View full text |Cite
|
Sign up to set email alerts
|

New dimensions in non‐classical neural computing, part II: quantum, nano, and optical

Abstract: Purpose -The purpose of this paper is to introduce new non-classical implementations of neural networks (NNs). The developed implementations are performed in the quantum, nano, and optical domains to perform the required neural computing. The various implementations of the new NNs utilizing the introduced architectures are presented, and their extensions for the utilization in the non-classical neural-systolic networks are also introduced. Design/methodology/approach -The introduced neural circuits utilize rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…buckyball), SWCNT, scanning electron microscopy (SEM) image of chemical vapor deposition (CVD) grown array of MWCNT towers, and an important example of CNT-based application in electronic systems as a channel in a FET. The newly emerging CNT technology has been implemented in many new promising applications (Al-Rabadi, 2007, 2009aAmaratunga, 2003;Bonard et al, 2002;Cheng et al, 2004;Collins and Avouris, 2000;Collins et al, 2001;Derycke et al, 2001;Drexler, 1986;Fujieda et al, 2005;Jiao et al, 2003;Likharev, 2003;Tomanek et al, 2002). These applications include TVs that are based on the field emission of CNTs that consume much less power, are thinner, and have much higher resolution than the best plasmabased TVs available; nanocircuits based on CNTs such as CNT-based FETs that consume less power and are much faster than the available silicon-based FETs; carbon nanocoils that can be used as inductors in nanofilters and as nanosprings in nano dynamic systems; and CNT rings.…”
Section: Cnts Characteristics and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…buckyball), SWCNT, scanning electron microscopy (SEM) image of chemical vapor deposition (CVD) grown array of MWCNT towers, and an important example of CNT-based application in electronic systems as a channel in a FET. The newly emerging CNT technology has been implemented in many new promising applications (Al-Rabadi, 2007, 2009aAmaratunga, 2003;Bonard et al, 2002;Cheng et al, 2004;Collins and Avouris, 2000;Collins et al, 2001;Derycke et al, 2001;Drexler, 1986;Fujieda et al, 2005;Jiao et al, 2003;Likharev, 2003;Tomanek et al, 2002). These applications include TVs that are based on the field emission of CNTs that consume much less power, are thinner, and have much higher resolution than the best plasmabased TVs available; nanocircuits based on CNTs such as CNT-based FETs that consume less power and are much faster than the available silicon-based FETs; carbon nanocoils that can be used as inductors in nanofilters and as nanosprings in nano dynamic systems; and CNT rings.…”
Section: Cnts Characteristics and Propertiesmentioning
confidence: 99%
“…The CNT is made from graphite, where it has been observed that graphite can be formed into nano-scale in three forms: carbon nanoball (or buckyball)a molecule composed of 60 carbon atoms (C 60 ) that are arranged in the form of a soccer ball; CNTnarrow strip of tiny sheet of graphite that comes mainly in two types: multi-walled CNT (MWCNT), where each CNT contains several hollow cylinders of carbon atoms nested inside each other, and single-walled CNT (SWCNT), which is made of just a single layer of carbon atoms; and carbon nanocoil. Implementations of basic logic gates such as the logic inverter using CNTs have been demonstrated (Derycke et al, 2001), engineering CNT circuits using electrical breakdown has been shown (Collins et al, 2001), the utilization of CNT-based films for cathode-based implementations has been demonstrated (Obraztsov et al, 2000), designing CNT multiplexer-based circuits and actuators has been shown (Al-Rabadi, 2007, 2009a, and the potential importance of CNTs for the design of electronic circuits and systems has been proposed (Collins and Avouris, 2000).…”
mentioning
confidence: 99%
“…This is due to the fact that reversible logic leads to the design of computer systems that consume much less power and occupy much less space [1,3,9,20,29,32,34], where it was shown that if all physical subcircuits were designed to be reversible then the whole system composed of inter-connecting these reversible sub-systems will minimize its operational need for power consumption [29]. For this purpose, various important technologies have been investigated to implement reversibility such as adiabatic CMOS circuits [36], optical computing [4] and quantum computation circuits and systems [1,2,4,15,20,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is a new emerging interdisciplinary field of research that covers several important science and technology areas of electronics, chemistry, physics and biology, which analyzes and synthesizes systems in the nano scale (10 -9 m) such as nanoparticles, nanowires and carbon nanotubes (CNTs) [4,7,8,14,15,17,29,30,33,35,44]. The CNT technology is one of many cutting-edge new technologies within nanotechnology which is showing high efficiency and a very wide range of applications in several various areas in science and engineering [3][4][5][6][7]9,12,14,15,17,24,28,30,35,36,41,44].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes have attracted attention in recent years not only for their relatively small dimensions and unique morphologies, but also for their potential implementations in many current and emerging technologies [3][4][5][6][7][8][9]12,14,15,17,24,[28][29][30]33,35,36,41,44]. The CNT is made from graphite [8,14,15,17,30,33].…”
Section: Introductionmentioning
confidence: 99%